A systematic review on the development and efficacy of nano-based vaccine in aquaculture - Ishaq, Shamsu Ibrahim; Anuar, Muhammad Salahudin Kheirel; Saba, Abdulwakil Olawale; Md Yasin, Ina Salwany; Che Abdullah, Che Azurahanim; Salleh, Annas; Nazarudin, Muhammad Farhan; Yusof, Mohd Termizi; Azmai, Mohammad Noor Amal (Springer Science and Business Media Deutschland GmbH, 2025)
Nano-based vaccine technology has become one of the solutions in aquaculture disease management as it provides enhanced immunity to the host organisms and reduces the use of antibiotics. This systematic review evaluates the nano-based vaccine development, formulations, and efficacy in improving animal survival rates, immune responses, and disease resistance, while identifying challenges and future directions of the nano-based vaccines technology in aquaculture. The reviews found that different nano-based vaccine formulations, such as chitosan nanoparticles, mesoporous silica nanocarriers, and biomimetic systems for DNA delivery, are proven to show high protective efficacy against pathogens such as Streptococcus agalactiae and Aeromonas hydrophila. Studies report survival rates between 83.3 and 96.2%, significant upregulation of immune markers and enhanced lysozyme activity. Nano-based vaccines also exhibit potent antibacterial activity, particularly in shrimp, with dsRNA-loaded nanoparticle vaccine improving survival by up to 80% against white spot syndrome virus. Although these developments are evident, the differences in the effect of the vaccine applications result from variations due to formulation strategies and host organisms of interest and variability in the environmental conditions remains a more significant hindrance. This review provides information regarding the potential applications of nano-based vaccine technology for the advancement of aquaculture that ensures disease control through the reduced use of antibiotics and sustainable global food security.